Breast abscess due to Actinomyces in a 14-year-old girl: First reported pediatric case - Randall S. Porter; Marjorie J. Arca; Geoffrey A. Weinberg; Michael H. Livingston (Elsevier, 2021)
A healthy 14-year-old girl presented to the emergency department with left breast pain and erythema. Ultrasound revealed a 1.8 cm complex fluid collection deep to the areola. The patient was admitted to hospital for a trial of intravenous cefazolin and warm compresses. The erythema improved and the collection drained spontaneously through the nipple-areolar complex. The drainage fluid grew Actinomyces radingae, and anaerobic Gram-positive cocci not further identified. The antibiotic regimen was changed to a four-month course of high-dose amoxicillin. Treatment was complicated by Clostridioides difficile colitis, which was treated with oral vancomycin on an outpatient basis. The patient otherwise recovered well with no significant scarring to the breast.